Hubungan Karakteristik dan Pengetahuan tentang Perencanaan Berkeluarga dengan Kesiapan Menikah Calon Pengantin di Kantor Urusan Agama Kecamatan Tambun Utara - Shella Fitriani; Sahrudi Sahrudi (Malahayati Nursing Journal, 2024)
ABSTRACT The high divorce rate in Indonesia is ranked first in Asia Pacific, and West Java is the province with the highest divorce after East Java, one of the factors causing divorce is the lack of readiness to marry. And the high interest of someone to get married raises the question of how the readiness for marriage of the prospective bride and groom at the KUA of North Tambun District, Bekasi. To determine the relationship between the characteristics and knowledge of family planning with the readiness to marry the bride and groom. This research uses descriptive analytic method with cross sectional design. The population of this study were all prospective brides who registered at the KUA of Tambun Utara District, the sample was determined by simple random sampling and the results obtained were 148 respondents. The data was tested with the chi square statistical test. In this study there is a relationship between age and readiness to marry with a p value (0.001). There is a relationship between work and marriage readiness with a p value (0.004). There is a relationship between education and marriage readiness with a p value (0.001). There is a relationship between family planning knowledge and marriage readiness with a p value (0.002). There are many factors that support readiness for marriage. The bride and groom are expected to better prepare for age, education, work and prepare knowledge about family readiness, so that a harmonious family is created and the nation's successors are proud. Keywords: Bride and Groom, Characteristics, Readiness for Marriage, Knowledge  ABSTRAK Tingginya angka perceraian di Indonesia yang menduduki peringkat pertama di Asia Pasifik, dan Jawa Barat merupakan provinsi dengan perceraian tertinggi setelah Jawa Timur, salah satu faktor penyebab terjadinya perceraian ialah kurangnya kesiapan menikah. Dan tingginya minat seseorang untuk menikah menimbulkan pertanyaan bagaimana kesiapan menikah calon pengantin di KUA Kecamatan Tambun Utara, Bekasi. Untuk mengetahui adanya hubungan karakteristik dan pengetahuan perencanaan berkeluarga dengan kesiapan menikah calon pengantin. Penelitian ini menggunakan metode deskriptif analitik dengan desain cross sectional. Populasi penelitian ini adalah seluruh calon pengantin perempuan yang mendaftarkan diri di KUA Kecamatan Tambun Utara, penentuan sampel dengan simple random sampling dan didapatkan hasil 148 responden. Data diuji dengan uji statistik chi square. Dalam penelitian ini ada hubungan antara usia dengan kesiapan menikah dengan p value (0,001). Ada hubungan pekerjaan dengan kesiapan menikah dengan p value (0,004). Ada hubungan antara pendidikan dengan kesiapan menikah dengan p value (0,001). Ada hubungan antara pengetahuan prencanaan berkeluarga dengan kesiapan menikah dengan p value (0,002). Terdapat banyak faktor yang mendukung kesiapan menikah. Pada calon pengantin diharapkan lebih mempersiapkan usia, pendidikan, pekerjaan dan menyiapkan tentang pengetahuan kesiapan berkeluarga, agar terciptanya keluarga yang harmonis dan penerus bangsa yang membanggakan. Kata Kunci: Calon pengantin, Karakteristik, Kesiapan menikah, Pengetahuan